Pelaksanaan Kegiatan Ekstrakurikuler Gamelan di Sekolah Dasar - Nadya nurul fauziah; Lutfi Nur (Edumaspul: Jurnal Pendidikan, 2022)
Gamelan extracurricular at school is an effort to improve students' musical skills as well as conservation efforts in the form of coaching. However, there are still many schools that are not good at implementing the gamelan extracurricular activities. Therefore, the purpose of this study is to provide information about the implementation of extracurricular activities by describing several things related to Gamelan learning, evaluation and achievements achieved by one of the elementary schools located in Sukaraja sub-district, Tasikmalaya district, including information about the process of training activities from the introduction. , core activities and closing up to the implementation of the evaluation. This study uses a survey method with a qualitative descriptive approach. Data were collected by observing school cases, interviews with related parties, and documentation in the form of pictures. The implication of this research activity is that the writer and the reader get important information about the process in gamelan extracurricular activities.